PERBANDINGAN LARUTAN BUAH PINANG (Arecha catechu L) DAN DAUN SIRIH HIJAU (Piper betle L) TERHADAP KEJELASAN JARINGAN HATI SEBAGAI ALTERNATIF PEWARNA ALAMI PREPARAT JARINGAN SEBAGAI SUMBER BELAJAR BIOLOGI - Dini Nur Oktaviani; Handoko Santoso (EDUBIOLOCK, 2020)
Fruit Arecha catechu L and leaf Piper betle L are plants that contain pigments that can be used as natural dyes for tissue preparations. This studyaims to determine the differences in liver tissue clarity using natural Arechacatechu L and leaf Piper betle L, determine the natural coloring solution ofArecha catechu L and Piper betle L the best for the clarity of tissuepreparations and research results can be used as a source of high schoolbiology learning in the form of practical instructions. Research conducted at the Integrated Science Laboratory of the Universitas of Muhammadiyah Metro in May 2019, the results of a photoanalysis of liver tissue preparations with natural dyes fruit Arecha catechu Lobtained percentage on criteria 1 "very clear and very contrast" (46.66%),criterion 2 "unclear and contrastless" (40%) and criterion 3 "unclear andnon-contrasting" (13.33%), while the percentage results obtained on photos ofliver tissue preparations with natural dyes of leaf solution Piper betle L incriterion 1 "very clear and very contrasting" (40%), criterion 2 "unclear andless contrasting" (40%) and criterion 3 "unclear and not contrasting" (20%).The results of this study were compiled as a source of learning biology in theform of practical instructions and validated by two expert lecturers, obtainingan average percentage of 88% with the criteria of "Very Good".